Handbook of research on information communication technology policy : trends, issues and advancements 2026-02-15T20:18:42+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Adomi, Esharenana E. (Information Science Reference, 2011)

(untitled)
"This book is a source book on information communication technology policies for those involved in ICT policy formulation, implementation, adoption, monitoring, evaluation and application"--Provided by publisher